Multinational enterprises and the law - Muchlinski, Peter (Oxford ; Cambridge, Mass. : Blackwell Publishers, 1995)
This text aims to offer a comprehensive treatment of the international legal environment. The book is divided into three parts, looking at the origins of MNE regulation, the limits of national or regional jurisdiction in the regulation of MNEs and the contribution of international law.
Includes index.
rpm 07/09/16
Loans
Keywords: International business enterprises -- Law and legislation; International business enterprises